## Answers by Jim S.

A vector that starts at A and ends at B is V=A-B. This vector also shows the direction of the line we are after.  Calculacting the components of V gives V(8,6,6) Just subtract the components of B from the components of A.   The eqqation of the line is R=X0+vt which in component...

x= first number y= second x=2y+9 and x+y=129, these are the equations...solving gives x=89,y=40   Hope this helps Jim

Y varies directly with x Means y=kx where k is a constant, we were told that when x=64 y=160 so k must be such that 160=64k or k=160/64 = 2.5 Sp now our equation is y=2.5x. When x=68 y= 2.5*68=170 Hope this helps Jim

An estimate of the probability of winning a prize is 7/30 or about 23%   Jim

Gordon,            I'm trying to make a doable problem out of your description, but alas I can't. Are you sure you copied it correctly? Jim

Kyle,         The slanted line forms the hypotenuse of a right triangle and is 53" long the height is 19.2" the width is the other leg of the triangle. Do you recall the  Pythagorean theorem? You v=can use it to solve fro the width.   &nb...

Lets say the -8 deg occurs at 0800 hrs and you are told that the temperature rose 2 deg every hour so the temperature T(t)=2*(t-8)-8 for t>=8. So at t=8 T(8)=-8 and at t-10 T(10)=4-8=-4   Make sense?   Jim

Hi Aleena,           The complement of event A is not A and p(A)+p(notA)=1 since the categories are mutual exclusive, i.e. a dog is not a cat. So p(not A)=1-p(A)=1-5/11=6/11.   Hope this helps   Jim

Hi Anna,           I you let w=width and l= length of the panel and p=perimeter =178. Then l=3w-11 and P=2l+2w So 178=2(3w-11)+2w 178=6w-22+2w 178=8w-22 8w=200 w=25" and l=64"   Hope this helps   Ji...

Hi Dan           We know that ax^2 + bx +c =y is the general equation for  quadratic function. You were given 4 points if you substuite any three points into the above equation you will have 3 equations for the three unknowns a,b, and c. You can then sub...

Hi Jennifer,       First the quadratic is symmetric i.e. when you replace x by-x you get the same result. y(x)=y(-x). whereas the exponential function is not symmetric.       Second the quadratic function has no unique inverse but the exponential does  ...

Hi Jodie,              Let H= no. of chickens      C= no. of cows So we know that H+C=29 (each has one head) We also know that 2H+4C=90 ( chickens have two and cows have 4 feet)   So you now have 2 equations...

Hi Kinsey,              Outside diameter of the tubing = 3 1/4" The outside radius is 1 5/8" (half the diameter). To find the inside radius we subtract the wall thickness from the outside radius which is 1 5/8 - 3/16 =1 7/16". to find the inside...

Take 1/2 the coefficient of x and square it (40/2)2 =400 Rewrite the equation adding and subtracting 400, (x2+40x+400)+c-400 This can be written as (x+20)2 +c-400 from which you can find the roots (x+20)2=400-c by taking+- the square root of both sides and solve...

Tanner,        You calculate the discounted cash flow for each time period and just add them up. When summed over all the time periods this quantity is sometimes called the "net present value" of the investment.   Jim

Jason,       If the the ball drawn was replaced this would a Bernoulli trail (independent trials and success probability is constant) then you would use at the binomial distribution. Since the success probability is not constant as mentioned in the other answers, you would...

Zoe,         Lets divide the rod into two segments left and right at .25m and .75m The center of mass of the segments are at .25/2 and .75/2 Taking moments (torque) about the given point gives ,25mg(,25/2)-.75mg(.75/2)=.6125-5.5125=4.9 N-m which is g/2   m=2kg...

The electric field E is defined by the force F it exerts on a positive test charge Qo. E=F/q0 and it is a vector.   Hope this helps   Jim

Nana         You have 3000=7.5*t2, so t=(3000/7.5)1/2 use your calculator.   Jim

John,      Since x-y=0 then x=y from the first equation   Putting x=y in the second equation gives -6y+5y=4 so y=-4 and x=-4.   The idea is to solve one of the equations for one of the unknowns and substuite that relationship in the second equation...